KETERLIBATAN AYAH DALAM PENGASUHAN TERHADAP KEMAMPUAN PENYESUAIAN DIRI ANAK USIA 4-6 TAHUN - Nurhani, Siti; Atika Putri, Azlin (Institut Agama Islam Negeri Langsa, 2020)
The involvement of fathers in the care of active participation of fathers in parenting that occurs continuously makes a positive impact on a child is one of them is adaptability. Adaptability is a person's ability to adapt well to itself or the environment, such as family, friends, other people, and the prevailing norms surrounding the environment. The purpose of this study was to determine the involvement of fathers is there a relationship in the care of the adaptability of children aged 4-6 years in kindergarten Kemala Bhayangkari 3 Pekanbaru. This type of research is research with a quantitative approach to the design of correlational research, for the study population was the father and learners TK Kemala Bhayangkari 3  Pekanbaru. Sample collection technique using a purposive sampling technique with a total sample of 40 children. The method used in this study is the use of grains statement attached to the questionnaire. Based on the calculation of correlation test obtained by r-value = 0.737, with significant value 0.000, then suggest a link between fathers' involvement in the care of the adaptability of children aged 4-6 years. In conclusion, the positive relationship between fathers' involvement in the upbringing of the adaptability of children aged 4-6 years in kindergarten Kemala Bhayangkari 3 Pekanbaru